Assessing territorial vulnerability: Testing a multidisciplinary tool in Moncalieri, Italy - Beltramino, Simone; Scalas, Mattia; Castro Rodriguez, David Javier; Brunetta, Grazia; Pellerey, Franco; Demichela, Micaela; Voghera, Angioletta; Longhi, Andrea; Mutani, Guglielmina; Caldarice, Ombretta; et al. (TeMA - Journal of Land Use, Mobility and Environment, 2022)
<span class="NormalTextRun SCXW125345616 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn=""ObjectId":"00000000-0000-0000-0000-000000000000|0","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",469777841,"Tahoma",469777842,"Tahoma",469777844,"Tahoma",469769226,"Tahoma",268442635,"18",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]">The challenge to make cities and human settlements inclusive, safe, and resilient, including mitigation and adaptation strategies against disaster, is a central issue in achieving sustainability. This research proposes a tool to measure local vulnerability from a multi-risk approach. The municipality of Moncalieri, Italy, was used as a case study within the research activities of the Responsible Risk Resilience Centre from the Polytechnic of Turin to test the vulnerability matrix. The tool consists of a mathematical framework for the territorial vulnerability assessment that integrates multiple indicators clustered into three factors defined as sensitivity, pressures, and hazards, weighted according to a participatory procedure. Space-dependent analyses using the Geographical Information System were developed from the multiple nested indicators to project the vulnerability index onto a homogeneous grid in the territory of interest. Thematic maps referring to the systemic vulnerability by different sensitivity components were generated. The tool not only contributes to increasing the awareness of territorial vulnerability but also offers support to resilience-based decision-making in designing technical measures of policies at a local scale. Further research is required to implement the framework in different scenarios and develop the model’s temporal behaviour.